Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure! Let's expand the expression [tex]\((a + 2b)^3\)[/tex] step by step using the binomial theorem.
The binomial theorem states that [tex]\((x + y)^n = \sum_{k=0}^{n} \binom{n}{k} x^{n-k} y^k\)[/tex], where [tex]\(\binom{n}{k}\)[/tex] is the binomial coefficient.
For our expression [tex]\((a + 2b)^3\)[/tex], we can set it up as follows:
[tex]\[ (a + 2b)^3 = \sum_{k=0}^{3} \binom{3}{k} a^{3-k} (2b)^k \][/tex]
Let's compute each term in the expansion step by step.
1. For [tex]\(k = 0\)[/tex]:
[tex]\[ \binom{3}{0} a^{3-0} (2b)^0 = 1 \cdot a^3 \cdot 1 = a^3 \][/tex]
2. For [tex]\(k = 1\)[/tex]:
[tex]\[ \binom{3}{1} a^{3-1} (2b)^1 = 3 \cdot a^2 \cdot (2b) = 6a^2b \][/tex]
3. For [tex]\(k = 2\)[/tex]:
[tex]\[ \binom{3}{2} a^{3-2} (2b)^2 = 3 \cdot a \cdot (2b)^2 = 3 \cdot a \cdot 4b^2 = 12ab^2 \][/tex]
4. For [tex]\(k = 3\)[/tex]:
[tex]\[ \binom{3}{3} a^{3-3} (2b)^3 = 1 \cdot 1 \cdot (2b)^3 = 1 \cdot 8b^3 = 8b^3 \][/tex]
Now, compile all these terms together:
[tex]\[ (a + 2b)^3 = a^3 + 6a^2b + 12ab^2 + 8b^3 \][/tex]
Therefore, [tex]\((a+2b)^3 = a^3 + 6a^2b + 12ab^2 + 8b^3\)[/tex].
The binomial theorem states that [tex]\((x + y)^n = \sum_{k=0}^{n} \binom{n}{k} x^{n-k} y^k\)[/tex], where [tex]\(\binom{n}{k}\)[/tex] is the binomial coefficient.
For our expression [tex]\((a + 2b)^3\)[/tex], we can set it up as follows:
[tex]\[ (a + 2b)^3 = \sum_{k=0}^{3} \binom{3}{k} a^{3-k} (2b)^k \][/tex]
Let's compute each term in the expansion step by step.
1. For [tex]\(k = 0\)[/tex]:
[tex]\[ \binom{3}{0} a^{3-0} (2b)^0 = 1 \cdot a^3 \cdot 1 = a^3 \][/tex]
2. For [tex]\(k = 1\)[/tex]:
[tex]\[ \binom{3}{1} a^{3-1} (2b)^1 = 3 \cdot a^2 \cdot (2b) = 6a^2b \][/tex]
3. For [tex]\(k = 2\)[/tex]:
[tex]\[ \binom{3}{2} a^{3-2} (2b)^2 = 3 \cdot a \cdot (2b)^2 = 3 \cdot a \cdot 4b^2 = 12ab^2 \][/tex]
4. For [tex]\(k = 3\)[/tex]:
[tex]\[ \binom{3}{3} a^{3-3} (2b)^3 = 1 \cdot 1 \cdot (2b)^3 = 1 \cdot 8b^3 = 8b^3 \][/tex]
Now, compile all these terms together:
[tex]\[ (a + 2b)^3 = a^3 + 6a^2b + 12ab^2 + 8b^3 \][/tex]
Therefore, [tex]\((a+2b)^3 = a^3 + 6a^2b + 12ab^2 + 8b^3\)[/tex].
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.